The Clinical Effect of Dapagliflozin in Patients with Angiographically Confirmed Coronary Artery Disease and Concomitant Type 2 Diabetes Mellitus - Yana Yu. Dzhun; Yevhen Yu. Marushko; Yanina A. Saienko; Nadiya M. Rudenko; Borys M. Mankovsky (Ukrainian Journal of Cardiovascular Surgery, 2022)
Nowadays treatment of patients with coronary artery disease (CAD) and concomitant type 2 diabetes mellitus (DM) needs further study.The aim. Evaluation of the clinical effect and glycemic variability of dapagliflozin in patients with angiographically confirmed CAD and concomitant type 2 DM.Materials and methods. The study involved 47 patients with angiographically confirmed CAD. The patients underwent laboratory blood tests, electrocardiography, echocardiography, continuous glucose monitoring and percutaneous coronary intervention (PCI). Depending on the usage of dapagliflozin 10 mg, the patients were divided into 2 groups: group I (+SGLT2i, n = 24) and group II (–SGLT2i, n = 23). The average follow-up period was 16 months.Results. Distribution of the examined patients by age, anthropometric characteristics, duration of DM, functional state of the heart and kidneys, smoking, the presence of acute cardiovascular events and previous PCI showed no statistically significant difference. In patients of group I, on the background of taking SGLT2i, a decrease in body mass index and improved glycemic profile were revealed. Patients in group II were more likely to have complaints of angina (4 [17.3%] vs 1 [4.3%], p>0.05); repeated coronary angiography in this group was significantly more likely to reveal progression to atherosclerotic CAD (4 [17.3%], p<0.05) which required re-revascularization. No fatalities were detected during the follow-up.Conclusion. Dapagliflozin has improved glycemic and lipid profile of the blood and long-term prognosis after PCI. Adding this drug to the treatment reduces the clinical progression of CAD, the need for re-hospitalization and cardiac revascularization.